Neural substrates of mnemonic discrimination: A whole‐brain fMRI investigation. Issue 3 (3rd February 2020) - Klippenstein, Jenna L.; Stark, Shauna M.; Stark, Craig E. L.; Bennett, Ilana J.
Abstract: Introduction: A fundamental component of episodic memory is the ability to differentiate new and highly similar events from previously encountered events. Numerous functional magnetic resonance imaging (fMRI) studies have identified hippocampal involvement in this type of mnemonic discrimination (MD), but few studies have assessed MD‐related activity in regions beyond the hippocampus. Therefore, the current fMRI study examined whole‐brain activity in healthy young adults during successful discrimination of the test phase of the Mnemonic Similarity Task. Method: In the study phase, participants made "indoor"/"outdoor" judgments to a series of objects. In the test phase, they made "old"/"new" judgments to a series of probe objects that were either repetitions from the memory set (targets), similar to objects in the memory set (lures), or novel. We assessed hippocampal and whole‐brain activity consistent with MD using a step function to identify where activity to targets differed from activity to lures with varying degrees of similarity to targets (high, low), responding to them as if they were novel. Results: Results revealed that the hippocampus and occipital cortex exhibited differential activity to repeated stimuli relative to even highly similar stimuli, but only hippocampal activity predicted discrimination performance. Conclusions: These findings are consistent with the notion that successful MD is supported by the hippocampus, with auxiliary processes supported by cortex (e.g., perceptual discrimination). Abstract : Mnemonic discrimination is a fundamental component of episodic memory that has typically been attributed to the hippocampus, with little attention paid to regions beyond the medial temporal lobe. Here, we examined neural signatures of mnemonic discrimination across the brain. Results revealed significant activity in hippocampus and occipital cortex, but only hippocampal activity predicted mnemonic discrimination performance.